2010
DOI: 10.1097/ccm.0b013e3181d8caaa
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of autoresuscitation after cardiac arrest*

Abstract: These findings suggest that the provision of cardiopulmonary resuscitation may influence autoresuscitation. In the absence of cardiopulmonary resuscitation, as may apply to controlled organ donation after cardiac death after withdrawal of life-sustaining therapies, autoresuscitation has not been reported. The provision of cardiopulmonary resuscitation, as may apply to uncontrolled organ donation after cardiac death, may influence observation time. However, existing evidence is limited and is consequently insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 49 publications
0
111
0
10
Order By: Relevance
“…However, autoresuscitation after failed CPR in adult cases has been seen up to 33 minutes after cessation of circulation in a recent analysis. 36 Further studies specific to the newborn population that document the incidence of autoresuscitation may be helpful in addressing these concerns cited by opponents of DCDD.…”
Section: Discussionmentioning
confidence: 99%
“…However, autoresuscitation after failed CPR in adult cases has been seen up to 33 minutes after cessation of circulation in a recent analysis. 36 Further studies specific to the newborn population that document the incidence of autoresuscitation may be helpful in addressing these concerns cited by opponents of DCDD.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The authors of the most recent systematic review, noting the low quality and limited scope of reports, concluded there are no cases of autoresuscitation without cardiopulmonary resuscitation. 22 Until a large observational study that provides narrow confidence intervals around the duration of autoresuscitation is conducted, this timing remains a prudential judgment. Once death is declared, there is no need for an additional waiting period before the initiation of organ recovery efforts.…”
Section: Declaration Of Deathmentioning
confidence: 99%
“…Trotzdem tritt es (auch bei Berück-sichtigung berichteter, aber medizinisch nicht publizierter Fälle) häufiger auf als angenommen. Der längste beobachtete Zeitraum zwischen Asystolie und Autoreanimation betrug 7 min nach Beenden der Reanimationsmaßnahmen [13].…”
Section: Das Phänomen Der Autoreanimationunclassified